2005
DOI: 10.1074/jbc.m500362200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Targeting of Transforming Growth Factor-β-activated Smad Complexes

Abstract: Upon stimulation by the transforming growth factor ␤ (TGF-␤), Smad2 and Smad3 are phosphorylated at their C termini and assemble into stable heteromeric complexes with Smad4. These complexes are the functional entities that translocate into the nucleus and regulate the expression of TGF-␤ target genes. Here we report that the TGF-␤-activated phospho-Smad3/Smad4 complex utilizes an importin-independent mechanism for nuclear import and engages different nucleoporins for nuclear import compared with the monomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 43 publications
5
62
0
2
Order By: Relevance
“…There is currently no explanation as to why the motifs are functional in Smad1 but not in Smad2 and 3. Nuclear export of Smad2 and 3 is clearly independent of CRM1, in both the absence and the presence of a TGF-b signal [18,19,24,27]. For Smad2, a karyopherin-independent export mechanism mediated by direct binding to nucleoporins has been suggested [19], similar to what was originally proposed for Smad2/3 import.…”
Section: Smad Export From the Nucleusmentioning
confidence: 50%
See 3 more Smart Citations
“…There is currently no explanation as to why the motifs are functional in Smad1 but not in Smad2 and 3. Nuclear export of Smad2 and 3 is clearly independent of CRM1, in both the absence and the presence of a TGF-b signal [18,19,24,27]. For Smad2, a karyopherin-independent export mechanism mediated by direct binding to nucleoporins has been suggested [19], similar to what was originally proposed for Smad2/3 import.…”
Section: Smad Export From the Nucleusmentioning
confidence: 50%
“…As it is the C-terminal phosphorylated serines in the R-Smads that are responsible for stabilizing the R-Smad-Smad4 complexes [14], these results suggested that R-Smad-Smad4 complexes dissociate in the nucleus as a result of R-Smad dephosphorylation, and that monomeric R-Smads and Smad4 are then exported separately by distinct mechanisms. In agreement with this idea, CRM1-dependent Smad4 export is thought to be inhibited by complex formation of Smad4 with R-Smads, which physically prevents Smad4 from interaction with CRM1 [27]. Moreover, R-Smad C-terminal phosphatases have recently been identified.…”
Section: Evidence For Smad Nucleocytoplasmic Shuttlingmentioning
confidence: 52%
See 2 more Smart Citations
“…The cytoplasmic/nuclear ratio is higher for the latent form because those forms associate with microtubule in the cytoplasm as well as specific anchor proteins such as SARA and dissociate from them upon TGFβ stimulation. Interaction of R-Smads to Smad4 also facilitates the retention of Smad4 in the nucleus [54,63,64]. In stimulated cells phosphorylated R-Smads/Smad4 complex enters the nucleus to regulate gene transcription, becomes dephosphorylated by a phosphatase [65], dissociates from each other, and exits the nucleus separately where R-Smads can be activated again.…”
Section: −2 Nuclear Translocation Of Smad Proteinsmentioning
confidence: 99%